KEPEMIMPINAN NON-MUSLIM: Konsep Wilāyah dalam al-Qur’an sebagai Basis Hukum Kepemimpinan Non-Muslim - K Kerwanto (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
One of the issues that often arise in the national politics and up to now is still warm is the rejection of non-Muslim leadership in the Muslim community.Responding to this issue, some scholars based on Qur’anic verses concluded that harm for Muslims makes non-Muslim leaders for the Muslim community.Acceptance of non-Muslim leadership is seen as a denial of God’s divine injunction and at the same time a submission to the reign of taghūt. This paper is intended to provide a different picture of thinking about non-Muslim leadership law. In this article, the author focuses on the discussion of the concept of wilāyah in the Qur’an because of the literal understanding of verses related to this concept that is often used as a basis for the prohibition of non-Muslim leadership. This article is an endorsement of the division of the concept of leadership in Islam into two parts as proposed by Muhsin Labib, namely:‘vertical (transcendental) and horizontal’ leadership. ‘A just non-Muslim and not hostile to Muslims’, for the author, may become a leader for Muslim society in the horizontal realm that does not require absolute divine legitimacy, but rather with relative humanitarian legitimacy. This kind of view, for the author, is more relevant to answer the indignation of some Muslim Indonesians living in heterogeneous communities.